PROFESSIONALIZATION OF NONPROFITS ORGANISATIONS, WHAT IMPACT ON NONPROFIT WORK CASE STUDY OF AMAS - LAHYA , Sarah; BENNIS , Laila (Revue Internationale du Chercheur, 2024)
The evolution of contemporary societies is inherently intertwined with the pivotal role played by associations in promoting local development. As key actors, they possess the capacity to catalyze positive changes within communities and contribute to enhancing the quality of life for their members. In recent decades, nonprofit organizations have undergone significant transformations that have altered their interactions with local actors, steering them towards professionalization to enhance their performance. While this evolution presents advantages, it may also impact the fundamental nature of social work and philanthropy. This article delves into a case study to understand and explore the challenges these organizations face as they seek to professionalize while preserving the essence of their existence. AMAS, a burgeoning association, has been prompted to reevaluate the role and significance of management in its associative project in order to professionalize. The approach adopted for this article is action research. The findings have facilitated an understanding of the professionalization logics and led to the formulation of recommendations to guide the professionalization of nonprofit activities.